К вопросу определения вины юридических лиц при совершении административных правонарушений - Chermit R. R., Ivanenko I. N. (Innovative technologies in science and education, 2017)
The article examines aspects of guilt of legal entities in the Commission of administrative offences
Keywords: административная ответственность; юридические лица; Legal entities; Administrative Offenses; вина юридического лица